Are unilateral devices valid for power output determination in cycling? insights from the favero assioma power meter - Valenzuela, P. L.; Montalvo-Perez, A.; Alejo, L. B.; Castellanos, M.; Gil-Cabrera, J.; Talavera, E.; Lucia, A.; Barranco-Gil, D. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Some power meters are available in both bilateral and unilateral versions. However, despite the popularity of the latter, their validity remains unknown. We aimed to analyze the validity of a unilateral pedal power meter for estimating actual ("bilateral") power output (PO).